PEMBELAJARAN MENULIS CERITA DENGAN MEDIA AUDIO VISUAL MELALUI MODEL PROBLEM BASED LEARNING - Sri Jumani; Mukti Widayati; Nurnaningsih; Rina Iriani Sri Ratnaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study describes the planning, implementation, obstacles, and solutions to learning story writing skills with audio-visual media through the Problem-Based Learning (PBL) model in Elementary Schools (SD). This study used qualitative descriptive research. The research strategy used in this study used a single embedded case study. Data sources are sources, places, events (activities), and documents or archives. Data collection is carried out through interviews, observation, and document analysis. Method triangulation techniques and data source triangulation do data validity. The data analysis technique used in this research is an interactive analysis model consisting of three activity lines: data reduction, data presentation, and conclusion drawing or verification. The results showed that teachers had prepared a reasonably complete lesson plan. The class teacher has done quite well, productively, and efficiently. The challenges presented by this learning include difficulty finding vocabulary and diction in writing stories, low student interest, less creative use of audiovisuals, and lack of teachers in mastering classes and materials. These obstacles are overcome by teachers multiplying learning resource books from magazines and the internet, designing learning that can attract students, designing learning plans that are as effective as possible, and procuring tools that can support the success of learning objectives. This finding also strengthens the opinion that through audiovisual media, PBL models for learning materials in Indonesia help students express and develop the results of their thoughts.